PENGARUH DISIPLIN KERJA, INTERNAL LOCUS OF CONTROL, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NON-PNS PADA UPTD PJI KALIGENDING - Wiwit Panggihraharjo; Dani Rizana (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2026)
This study aims to analyze the effect of work discipline, internal locus of control, and motivation on the performance of non-civil servant employees at UPTD PJI Kaligending, Kebumen Regency. This research employed a quantitative approach using a survey method involving 35 respondents. Data were analyzed using multiple linear regression, with hypothesis testing conducted through t-tests, F-tests, and the coefficient of determination (R²). The results indicate that partially, work discipline, internal locus of control, and motivation have a positive and significant effect on performance. Simultaneously, the three independent variables also significantly influence employee performance. The coefficient of determination shows that 68.4% of the variance in performance can be explained by the independent variables included in the model, while the remaining 31.6% is influenced by other factors not examined in this study. These findings highlight the importance of strengthening behavioral, psychological, and motivational aspects in improving employee performance.